2019
DOI: 10.1016/j.schres.2018.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive control network dysconnectivity and response to antipsychotic treatment in schizophrenia

Abstract: To better understand cognitive control impairment in schizophrenia, it is vital to determine the extent of dysfunctional connectivity in the associated fronto-striatal brain network, with a focus on the connections with the anterior cingulate cortex (ACC), prior to the potential confounding effect of medication. It is also essential to determine the effects following antipsychotic medication and the relationship of those effects on psychosis improvement. Twenty-two patients with schizophrenia, initially unmedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…Moreover, the regions involved in the respective networks appear to overlap, with connections to the anterior cingulate and frontal cortex altered in both. 27,28 Overall, our data suggest that poor treatment response in schizophrenia is related to altered connectivity across a distributed set of brain regions, rather than focal morphological alterations in a specific area. This is coherent with both the inconsistency and the large variability of findings reported in previous studies of focal neuromorphological correlates of psychosis outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, the regions involved in the respective networks appear to overlap, with connections to the anterior cingulate and frontal cortex altered in both. 27,28 Overall, our data suggest that poor treatment response in schizophrenia is related to altered connectivity across a distributed set of brain regions, rather than focal morphological alterations in a specific area. This is coherent with both the inconsistency and the large variability of findings reported in previous studies of focal neuromorphological correlates of psychosis outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…Connectomics provides a reference for evaluating the efficacy of antipsychotics in schizophrenia. By analyzing MRI data of 22 patients and 20 healthy controls, Cadena et al found that greater functional connectivity between anterior cingulate cortex and bilateral putamen at baseline predicted subsequent better treatment response (32). To investigate whether resting-state functional connectivity is associated with long-term clinical outcomes of patients with schizophrenia, Lee et al found that poorer clinical outcomes in patients with schizophrenia were associated with decreased DMN connectivity (33).…”
Section: Application Of Connectome In Diagnosis Of Schizophreniamentioning
confidence: 99%
“…By analyzing MRI data of 22 patients and 20 healthy controls, Cadena et al. found that greater functional connectivity between anterior cingulate cortex and bilateral putamen at baseline predicted subsequent better treatment response ( 32 ). To investigate whether resting-state functional connectivity is associated with long-term clinical outcomes of patients with schizophrenia, Lee et al.…”
Section: Magnetic Resonance Imaging-based Connectomics In First-episomentioning
confidence: 99%
“…Researchers have used the Stroop effect as one way to study the IC deficit in schizophrenia and other psychotic disorders ( Laurenson et al, 2015 ). Prior studies have shown that people experiencing psychosis are slower and less accurate in the interference condition of Stroop test than healthy controls ( Cadena et al, 2019 ; Popov, Kustermann, Popova, Miller, & Rockstroh, 2019 ) and this difference in performance is not related with premorbid IQ ( Martin, Mowry, Reutens, & Robinson, 2015 ), or affective symptoms ( Tyburski et al, 2017 ), or other cognitive processes ( Ettinger et al, 2018 ). Also, the negative effect of ageing in Stroop performance is more pronounced in psychosis, which suggests that IC decline associated to aging starts earlier in psychosis ( Thuaire et al, 2020 ).…”
mentioning
confidence: 94%